321 UNMET NEEDS AFTER STROKE. (25th October 2022) - Harte, G; Keane, J; Ryan, D; Collins, R; Garcia, C; Howlin, R; Ryan, S; Connolly, A; Leitch, E; Moynan, W; Healy, S; Keenan, M
Abstract: Background: Unmet needs, such as lack of access to rehabilitation, support and information, are experienced by a high proportion of stroke survivors after discharge from acute and rehabilitation services. The UK guidelines on stroke (2016) recommend that all patients should be offered a structured health and social care review at 6 months post-stroke. However, no such clinics exist to date in Ireland. We aimed to explore the extent of unmet needs in the catchment area of a large teaching hospital. Methods: A random selection of patients 6-months post-stroke were contacted by telephone and unmet needs were assessed using a validated tool, Post-Stroke Checklist. Following analysis of data, the need for a pilot clinic was identified. A separate random selection of patients discharged from acute services 6 months previously were invited to attend a review clinic. Patients were assessed using an adapted version of the Greater Manchester Stroke Assessment Tool. Assessments were conducted jointly by a physiotherapist and a speech and language therapist, and appropriate onward referrals were made. Results: Telephone clinic : 51 patients completed the checklist. The most prevalent symptoms reported were fatigue (75%), reduced participation in hobbies and activities, decline in cognition (61%) and mobility problems (59%). Review clinic : 21 patients attended. The most prevalent symptoms reported were reduced memory/concentration (71%), low mood (71%), unintentional weight loss/gain (62%), and reduced mobility (43%). Onward referrals were made for in 16/21 (76%) cases; physiotherapy (n=12), occupational therapy (n=7), speech and language therapy (n=7), clinical nutrition (n=5), social work (n=7), psychology (n=5). Conclusion: Data from this exploratory study supports previous research indicating a high number of stroke survivors with unmet needs. This highlights the importance of establishing post-acute stroke review clinics and pathways in the Irish setting.